First record of the assassin bugs Zelus renardii Kolenati, 1857 (Heteroptera, Reduviidae) in Uzbekistan - Musaev, Dilshod M.; Akhmedov, Askar G.; Mirzaeva, Gulnara S.; Kholmatov, Bakhtiyor R.; Medetov, Makhset Zh. (Acta Biologica Sibirica, 2023)
This study was conducted in Tashkent in 2022 – 2023. As a result of this study, the species Zelus renardii Kolenati, 1857, was discovered for the first time for the fauna of Uzbekistan. Zelus renardii is an invasive species that has recently been actively spreading in new territories for it. Most likely, the samples we found were imported to Uzbekistan from Turkey.